Changing patterns of multidisciplinary team treatment, early mortality, and survival in colorectal cancer. Issue 5 (18th October 2022) - Layfield, David M; Flashman, Karen G; Benitez Majano, Sara; Senapati, Asha; Ball, Christopher; Conti, John A; Khan, Jim S; O'Leary, Daniel P
Abstract: Background: This study reports early mortality and survival from colorectal cancer in relation to the pattern of treatments delivered by the multidisciplinary team (MDT) meeting at a high-volume institution in England over 14 years. Methods: All patients diagnosed with colorectal cancer and discussed during MDT meetings from 2003 to 2016 at a single institution were reviewed. Three time intervals (2003–2007, 2008–2012, and 2013–2016) were compared regarding initial surgical management (resection, local excision, non-resection surgery, and no surgery), initial oncological therapy, 90-day mortality, and crude 2-year survival for the whole cohort. Sub-analyses were performed according to age greater or less than 80 years. Results: The MDT managed 4617 patients over 14 years (1496 in the first interval and 1389 in the last). Over this time, there was a reduction in emergency resections from 15.5 per cent to 9.0 per cent ( P < 0.0001); use of oncological therapies increased from 34.6 per cent to 41.6 per cent ( P < 0.0001). The 90-day mortality after diagnosis of colorectal cancer dropped from 14.8 per cent to 10.7 per cent ( P < 0.001) and 2-year survival improved from 58.6 per cent to 65 per cent ( P < 0.001). Among patients aged 80 years or older (425 and 446, in the first and last intervals respectively) there was, in addition, a progressive increase in 'no surgery' rate from 33.6 per cent to 50.2 per cent ( P < 0.0001) and a reduction in elective resections from 42.4 per cent to 33.9 per cent ( P = 0.010). The 90-day mortality after elective resection fell from 10.0 per cent (18 of 180) to 3.3 per cent (5 of 151; P = 0.013). Conclusions: Survival from colorectal cancer improved significantly over 14 years. Among patients aged ≥80 years, major changes in the type of treatment delivered were associated with a decrease in postoperative mortality. Abstract : This report highlights the possibility that, in addition to improving survival from individual treatments, a multidisciplinary team may improve its outcomes by doing more or less of particular treatments.